The Development and Applications of a Dual Optical Imaging System for Studying Glioma Stem Cells - Po-An Tai MD, PhD; Yen-Lin Liu MD, PhD; Ya-Ting Wen MD; Chien-Min Lin MD, PhD; Thanh-Tuan Huynh MD, PhD; Michael Hsiao DVM, PhD; Alexander T. H. Wu PhD; Li Wei MD, PhD (Molecular Imaging)
Glioblastoma multiforme represents one of the deadliest brain tumor types, manifested by a high rate of recurrence and poor prognosis. The presence of glioma stem cells (GSCs) can repopulate the tumor posttreatment and resist therapeutics. A better understanding of GSC biology is essential for developing more effective interventions. We established a CD133 promoter-driven dual reporter, expressing green fluorescent protein (GFP) and firefly luciferase (CD133-LG), capable for in vitro and in vivo imaging of CD133+ GSCs. We first demonstrated the reporter enabled in vitro analyses of GSCs. DBTRG-05MG (Denver Brain Tumor Research Group 05) carrying CD133-LG (DBTRG-05MG-CD133-LG) system reported increased GFP/luciferase activities in neurospheres. Additionally, we identified and isolated CD133+/GFP+ cells with increased tumorigenic properties, stemness markers, Notch1, β-catenin, and Bruton’s tyrosine kinase (Btk). Furthermore, prolonged temozolomide (TMZ) treatment enriched GSCs (reflected by increased percentage of CD133+ cells). Subsequently, Btk inhibitor, ibrutinib, suppressed GSC generation and stemness markers. Finally, we demonstrated real-time evaluation of anti-GSC function of ibrutinib in vivo with TMZ-enriched GSCs. Tumorigenesis was noninvasively monitored by bioluminescence imaging and mice that received ibrutinib showed a significantly lower tumor burden, indicating ibrutinib as a potential GSC inhibitor. In conclusion, we established a dual optical imaging system which enables the identification of CD133+ GSCs and screening for anti-GSC drugs.